2017
DOI: 10.3348/kjr.2017.18.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Essential Items for Structured Reporting of Rectal Cancer MRI: 2016 Consensus Recommendation from the Korean Society of Abdominal Radiology

Abstract: High-resolution rectal MRI plays a crucial role in evaluating rectal cancer by providing multiple prognostic findings and imaging features that guide proper patient management. Quality reporting is critical for accurate effective communication of the information among multiple disciplines, for which a systematic structured approach is beneficial. Existing guides on reporting of rectal MRI are divergent on some issues, largely reflecting the differences in overall management of rectal cancer patients between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…With specific regard to rectal cancer MRI staging, a systematic approach to standardize the reporting process was first described in 2008 [60] and shortly after the same working group proposed a SR template including all relevant key imaging findings [61]. Interestingly, in 2014 a synoptic MRI report was successfully developed, and pilot tested in Ontario (Canada), with a 37% adoption rate across the province and leading to a 39% improvement in MRI reports completeness [62]. More recently, the results of scientific societies consensus meetings focused on rectal cancer MRI staging have been released, defining essential items and SR templates for structured reporting [63,64].…”
Section: Rectal Cancermentioning
confidence: 99%
“…With specific regard to rectal cancer MRI staging, a systematic approach to standardize the reporting process was first described in 2008 [60] and shortly after the same working group proposed a SR template including all relevant key imaging findings [61]. Interestingly, in 2014 a synoptic MRI report was successfully developed, and pilot tested in Ontario (Canada), with a 37% adoption rate across the province and leading to a 39% improvement in MRI reports completeness [62]. More recently, the results of scientific societies consensus meetings focused on rectal cancer MRI staging have been released, defining essential items and SR templates for structured reporting [63,64].…”
Section: Rectal Cancermentioning
confidence: 99%
“…In addition, both the examiner and the referring clinician often have a preference for SRs in these studies due to higher levels of accuracy and clarity [1014]. This may result in a better understanding of the pathology and its therapeutic implications [15, 16]. A healthcare professional using a SR is less likely to omit important structures.…”
Section: Introductionmentioning
confidence: 99%
“…A Likert scale-based structured reporting (SR) form may be an effective measure for successful standardization. The need for SR has long been recognized in the field of radiology (101112). However, recent surveys (1314) showed that the SR is rarely used in practice except for breast (15) or cardiac imaging (16).…”
Section: Introductionmentioning
confidence: 99%